Identifying inherited metabolic disorders in children: the role of elevated creatine kinase - Merve Yoldaş Çelik; Burcu Köşeci (BMC Pediatrics)
Abstract Introduction Elevated creatine kinase (CK) levels are key indicators of muscle injury and are commonly used in the differential diagnosis of pediatric disorders, particularly inherited metabolic disorders (IMDs). However, variability in CK elevation and the absence of standardized diagnostic thresholds complicate its clinical interpretation. This study aimed to evaluate the diagnostic utility of CK levels in distinguishing IMDs from other etiologies and to identify clinical and biochemical patterns that could facilitate earlier recognition of IMDs. Methods We retrospectively analyzed 1,660 pediatric patients seen at a metabolic clinic, identifying 320 (19.3%) who had CK measurements. Among them, 99 patients (30.9%) had elevated CK levels (> 171 U/L). These patients were divided into three diagnostic groups: idiopathic, IMD-diagnosed, and other diseases. “Idiopathic” referred to cases without a confirmed diagnosis. Biochemical parameters (CK, AST, LDH) were compared, and receiver operating characteristic (ROC) analysis was performed. Results Thirteen patients (15.1%) were diagnosed with IMDs. The IMD group showed significantly higher CK and AST levels compared to the idiopathic group (p < 0.05). ROC analysis indicated that a CK cut-off of 617.5 U/L had a sensitivity of 61.5% and specificity of 88.0% for identifying IMDs. However, CK alone could not effectively distinguish other diseases from idiopathic cases. Advanced metabolic investigations and comprehensive clinical evaluations were essential for accurate diagnosis. Conclusion While CK levels offer useful preliminary diagnostic information, they must be interpreted alongside advanced metabolic testing and clinical findings for reliable diagnosis. This study emphasizes the value of a multidisciplinary approach in assessing elevated CK levels in pediatric patients and calls for further research to optimize diagnostic pathways.